Hubungan Usia, Status Gizi, dan Durasi Kerja dengan Kelelahan Kerja pada Pekerja Industri Tahu di Wonogiri - Fatmasari, Wahida Fitria; Astuti, Dwi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Work fatigue is characterized by a shift in the body's condition from energetic to one of weakness. Fatigue arises from an imbalance between physical and mental capacity during activity and serves as the body's and brain's recovery mechanism. This study aims to determine the relationship between age, nutritional status, and work duration with work fatigue among tofu industry workers in Wonogiri. The research method was quantitative with a cross-sectional design. The sample includes 48 workers from nine tofu industries. We collected data through the Subjective Self-Rating Test (SSRT) questionnaire and demographic data. Data Analysis used the Spearman Rank and Mann-Whitney tests. The results showed that age was significantly related to work fatigue (p=0,000; r=0,552), while nutritional status (p=0,760) and work duration (p=0,117) did not show a significant relationship.